CRIMINOLOGICAL CHARACTERISTICS OF JUVENILE DELINQUENCY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article analyzes the criminological characteristics of juvenile delinquency. The features inherent in this type of crime are highlighted. The most common criminal acts committed by minors are listed.